Hungarian Monitoring, 21 March 1990 . [Magyar rádiófigyelő], 1990. március 21 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Moscow and Lithuanian independence - German re-unification process - International reactions to bloody events in Targu Mures Domestic Affairs: - Situation close to civil war in Targu Mures - Interview with András Sütő - Visa system with FRG lifted - Elections: rallies, press conferences - Ágnes Heller on the democratization process Economy: - Costs of the Gabčíkovo-Nagymaros dam investment - No agreement at Hungarian-Soviet economic talks Külpolitika: - Moszkva és a litván függetlenség - Német újraegyesítési folyamat - A marosvásárhelyi véres események külföldi visszhangja Belpolitika: - Polgárháborúhoz közeli állapotok Marosvásárhelyen - Interjú Sütő Andrással - Megszűnik a vízumkényszer az NSZK-val - Választás: nagygyűlések, sajtótájékoztatók - Heller Ágnes a demokratizálás folyamatáról Gazdaság: - A Bős-Nagymarosi beruházás költségei - Nincs egyezség a magyar-szovjet gazdasági tárgyalásokon